COVID-19 and ophthalmic herpes zoster co-infection in immunocompetent patient - Sissy, Sissy; Santoso, Adeline; Gotama, Dewi; Rusyati, Luh Made Mas (Bali Dermatology and Venereology Journal, 2021)
Background: Varicella-zoster virus (VZV) is a virus of human neurotropic that remains within ganglionic neurons in a latent state after the primary infection throughout the entire neuroaxis.Case: A male patient, 32 years old Javanese, consulted from the pulmonary division with complaints of vesicular eruption in the facial area on September 27, 2020. The patient was diagnosed with ophthalmic herpes zoster and a mild COVID-19 infection since 2 days ago and was hospitalized. Management in patients was acyclovir, methylprednisolone, with analgesics and vitamins. COVID-19 as co-infection and other viruses has been known, but infrequently affect the respiratory tract.Conclusion: Herpes zoster patient should ruled out the COVID-19 and maximize the precaution for personal safety equipment until the SARS-CoV-2 is excluded.